2013
DOI: 10.1007/s10840-012-9775-1
|View full text |Cite
|
Sign up to set email alerts
|

Posteroseptal accessory pathway in association with coronary sinus diverticulum: electrocardiographic description and result of catheter ablation

Abstract: Our total initial failure rate and subsequent recurrence was around 41 %. Better results might have been achieved had we applied irrigated tip catheters or NavX(TM)-guided cryoablation or subxiphoid epicardial mapping and ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 18 publications
1
27
0
6
Order By: Relevance
“…Approximately 19%–33% of accessory pathways can lie near or within the coronary sinus (CS) ostium, proximal CS, or CS diverticulum, 13 often referred to as inferior paraseptal (and previously posteroseptal) accessory pathways. 4 Although accessory pathway–mediated AV reentrant tachycardia can be managed pharmacologically, radiofrequency catheter ablation has become a well-established treatment option for these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 19%–33% of accessory pathways can lie near or within the coronary sinus (CS) ostium, proximal CS, or CS diverticulum, 13 often referred to as inferior paraseptal (and previously posteroseptal) accessory pathways. 4 Although accessory pathway–mediated AV reentrant tachycardia can be managed pharmacologically, radiofrequency catheter ablation has become a well-established treatment option for these patients.…”
Section: Introductionmentioning
confidence: 99%
“…In the procedure in this case, the electrode impedance was unstable during the initial ablation and a change of the ablation catheter was required, which might have resulted in the tip coming in contact with the aneurysm. The previous reports described that there was a lower success rate and higher complication rate of catheter ablation of accessory pathways related to CS aneurysms . Our case would indicate that a CS angiogram might be recommended in cases in which the catheter tip impedance or temperature is too unstable during radiofrequency delivery during PJRT ablation.…”
Section: Discussionmentioning
confidence: 56%
“…The previous reports described that there was a lower success rate and higher complication rate of catheter ablation of accessory pathways related to CS aneurysms. 8,9 Our case would indicate that a CS angiogram might be recommended in cases in which the catheter tip impedance or temperature is too unstable during radiofrequency delivery during PJRT ablation. If CS anomaly was found, contact force monitoring would be useful for a successful ablation and to avoid complications.…”
Section: Discussionmentioning
confidence: 90%
“…Second, this study did not include patients with an epicardial accessory pathway. Previous studies reported that a posteroseptal accessory pathway traversed the subepicardial region in some patients. In these cases, negative deflection of the retrograde P wave in the inferior leads may become large.…”
Section: Discussionmentioning
confidence: 95%